Prognostication in emergency room patients: comparing ultrasensitive and contemporary quantification of cardiac troponin levels below the 99th percentile - Anna Carrasquer; Anna Carrasquer; Anna Carrasquer; Germán Cediel; Germán Cediel; Germán Cediel; Alma Gómez-Sanz; Alma Gómez-Sanz; Óscar M. Peiró; Óscar M. Peiró; Óscar M. Peiró; Isabel Fort-Gallifa; et al. (Frontiers in Cardiovascular Medicine)
IntroductionCardiac troponin levels below the 99th percentile improve the predictive efficacy for cardiovascular events when associated with relevant clinical variables. However, whether ultra-sensitive analytical methods improve this predictive efficacy over less sensitive or contemporary analytical methods remains unknown.MethodsThis retrospective observational study involved consecutive patients who presented to the emergency department for suspected acute coronary syndrome and underwent measurement of ultra-sensitive cardiac troponin I (Singulex) and contemporary cardiac troponin I (Siemens) with levels below the 99th percentile. The clinical characteristics of these patients were analysed, and the efficacy of both analytical methods for predicting cardiovascular events over a 4-year follow-up period was compared.ResultsIn total, 838 patients were analysed (mean age, 62.9 ± 16.6 years; 42.2% women). Their cumulative incidence of the composite cardiovascular event (death, readmission for myocardial infarction, and readmission for heart failure) was 25.9% over the 4-year follow-up. Both Singulex cardiac troponin I (analysed by quartiles) and Siemens cardiac troponin (analysed as detectable/undetectable) improved the predictive efficacy for the combined event over clinical variables [Harrell's C-index (95% confidence interval): 0.77 (0.74–0.80) vs. 0.79 (0.76–0.81) and 0.77 (0.74–0.80) vs. 0.78 (0.75–0.81), respectively; p = 0.018]. However, there were no statistically significant difference between the two predictive models that included the aforementioned troponin assays.ConclusionsDetectable levels of cardiac troponin using a contemporary analytical method or those near the 99th percentile using an ultra-sensitive analytical method improve the predictive efficacy for cardiovascular events, with no differences between the two methods